Optimum receiver evaluation of ultra wideband impulse radio based on measurements data - Phroasamniang, Amphon; Promwong, Sathaporn (My University, 2011)
Ultra wideband impulse radio (UWB-IR) technology is an ideal candidate for wireless UWB that can be utilized for short-range, high-speed, low power, and low cost indoor applications. The transmission gain of the free space propagation loss is usually estimated by using Friis' transmission formula. The Friis formula, it is not directly applicable to ultra wideband impulse radio network transmission systems, in particular the single band impulse radio, as the formula is expressed as a function of the frequency. Moreover, the waveform may be distorted due to the frequency characteristics of the antenna, and the comparison between Tx and Rx waveforms is not straightforward. This paper discusses the free space link budget evaluation of UWB antenna with template receiver based on the extended Friis' transmission formula. The template is considered at the receiver side to maximize the SNR for evaluation. An experimental evaluation of the complex transfer function needs the three-antenna method for the calibration of reference antenna. The technique gives very accurate results and is very useful for design and evaluation of UWB transmission performance, especially for the evaluation of waveform distortion effects. © 2011 IEEE.
Keywords: Friis' transmission formula; impulse radiok; transmission gain; UWB antenna; UWB-IR